Modal Sosial Dalam Manajemen Bumdes; Konsep, Antesenden dan Konsekuensi - Baretha Meisar Titioka; Mugi Harsono; Astrid Jacquelen Debby Siahainenia (Univiversitas Dr. Djar Wattiheluw, 2023)
Social capital is a concept that is still relevant and contextual in responding to the socio-economic dynamics that live and develop in society. The essence of the concept of social capital is the construction of beliefs, norms, and social networks, whose dimensions are cognitive, structural, and relational. The purpose of this article is to examine the concept of social capital from the aspects of ontology, epistemology, and axiology. To support this research, a literature review is used as a methodology, explaining the emergence of the concept of social capital, further developing the theory of social capital, and reviewing the results of previous studies. The purpose of this study is to provide a more comprehensive picture of the concept of social capital that can be used in the context of managing Village Owned Enterprises (BUMDes), taking into account its antecedents and consequences to provide research material on the relationship of social capital in BUMDes management.